2018
DOI: 10.1177/1477760618798425
|View full text |Cite
|
Sign up to set email alerts
|

The performance and durability of polyethylene terephthalate and crumb rubber–modified road pavement surfaces

Abstract: This research investigates the influence of waste polymeric polyethylene terephthalate (PET) materials obtained from waste plastic bottles and crumb rubber (CR) obtained from used automobile tyres on the performance (Marshall stability, flow and compression) and durability (weathering) characteristics of road-paving material made from Trinidad Petroleum Bitumen and the world-renowned Trinidad Lake Asphalt. Apart from possibly serving as additives to improve performance, incorporating waste PET and CR in asphal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…These disadvantages are eliminated by an innovative modifying additive-expanded Kulantau vermiculite, which is a complex modifier designed to improve the asphalt concrete mixture during its preparation. Several studies have evaluated the possibility of using residues to make asphalt mixtures [20][21][22][23][24][25][26][27].…”
Section: Discussion Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These disadvantages are eliminated by an innovative modifying additive-expanded Kulantau vermiculite, which is a complex modifier designed to improve the asphalt concrete mixture during its preparation. Several studies have evaluated the possibility of using residues to make asphalt mixtures [20][21][22][23][24][25][26][27].…”
Section: Discussion Of Methodsmentioning
confidence: 99%
“…These disadvantages are eliminated by an innovative modifying additive-expanded Kulantau vermiculite, which is a complex modifier designed to improve the asphalt concrete mixture during its preparation. Several studies have evaluated the possibility of using residues to make asphalt mixtures [20][21][22][23][24][25][26][27]. The spectra obtained through IR spectroscopy, following the methodology for conducting a comparative analysis of the chemical composition of compounds, were overlaid with scaling based on CH2 groups, with content independent of experimental conditions.…”
Section: Discussion Of Methodsmentioning
confidence: 99%
“…Production of plastic containers from pellets is a quicker and much cheaper process compared to the recycling and reuse processes this brings about a continuous increase in the generation of PET (Hopewell et al, 2009;Thompson et al, 2009). The rising-rate at which these plastic wastes are disposed cause negative impacts such as visual pollution, flooding, endangerment of sea animals, and wildlife (Maharaj et al, 2019;Bamigboye et al, 2019) PET has also made grave economic impacts. A report by Weber and Kroll (2019) states that plastic waste results in damages to the marine ecosystem worth US$13 billion annually.…”
Section: Polyethylene Terephthalate (Pet) Plastic Bottlesmentioning
confidence: 99%
“…The Modulus of Resilience (M R ) decreased with increasing PET content due to the reduction of internal friction between particles. Maharaj et al (2019) reported on the durability and performance of road pavement surfacing with PET and Crumb rubber (CR). Marshal mix results showed that the optimum content of PET and CR polymer is 1% and 5% respectively.…”
Section: Utilization Of Selected Wastes In Road Constructionmentioning
confidence: 99%
“…Another important sector of use of ELTs is that of roads and infrastructures where, in addition to silent and long-lasting "modified" asphalts, there are cycle paths, street furniture, and elements for road safety. [6][7][8][9] These most common applications of ELT powder either use this material as a filler or a virgin polymer, such as EVA (Ethylene-vinyl acetate), is used as a binder.…”
Section: Introductionmentioning
confidence: 99%